2018
DOI: 10.1111/jipb.12612
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci associated with soybean seed weight and composition under different phosphorus levels

Abstract: Seed size and composition are important traits in food crops and can be affected by nutrient availability in the soil. Phosphorus (P) is a non-renewable, essential macronutrient, and P deficiency limits soybean (Glycine max) yield and quality. To investigate the associations of seed traits in low- and high-P environments, soybean recombinant inbred lines (RILs) from a cross of cultivars Fiskeby III and Mandarin (Ottawa) were grown under contrasting P availability environments. Traits including individual seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
5
23
0
Order By: Relevance
“…Therefore, improving P efficiency has become an important target in breeding programmes seeking to improve soybean production. QTL mapping in relation to low P tolerance in soybean have been conducted (Hacisalihoglu et al., 2018; Li et al., 2005; Song et al., 2014; Yang et al., 2019; Zhang, Cheng, et al., 2009; Zhang, Li, et al., 2016; Zhang, Liu, et al., 2009; Zhang et al., 2014; Zhang, Zhang, et al., 2016). By combining linkage analysis and genome‐wide association study (GWAS), Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving P efficiency has become an important target in breeding programmes seeking to improve soybean production. QTL mapping in relation to low P tolerance in soybean have been conducted (Hacisalihoglu et al., 2018; Li et al., 2005; Song et al., 2014; Yang et al., 2019; Zhang, Cheng, et al., 2009; Zhang, Li, et al., 2016; Zhang, Liu, et al., 2009; Zhang et al., 2014; Zhang, Zhang, et al., 2016). By combining linkage analysis and genome‐wide association study (GWAS), Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Using molecular markers for indirect selection of important agronomic traits, and molecular marker-assisted selection (MAS) could improve the e ciency of traditional plant breeding [5,6]. In last three decade years, numerous quantitative trait loci (QTL) for oil content in soybean seed have been reported [5,[7][8][9][10][11][12][13], about 327 oil QTLs listed in the Soybase Database (http://www.soybase.org). And a few soybean oil content QTLs have been identi ed in multi-environment and multi-genetic backgrounds [5,7,14].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [15] integrated QTLs from soybean at different growth stages and identified 10 QTLs controlling multiple growth stages in five linkage groups (C2, D1a, D1b, F and J). Hacisalihoglu et al [16] performed QTL mapping of a soybean RIL population grown in environments with different levels of P availability, and found that QTLs controlling seed quality and volume on Gm06 shared overlapping regions. The use of these types of loci could help improve multiple agronomic traits in soybean, thereby increasing the yield and quality of this important crop.…”
Section: Introductionmentioning
confidence: 99%